Konformitas Kelompok dan Polikulturalisme pada Mahasiswa Perantau - Alya Fikriyati; Muhammad Fath Mashuri; Diah Karmiyati (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2021)
The level of conformity determines personal unwillingness to engage with another social group. Conformity is a type of individual adaptability to a social group affected by social influence. Polyculturalism is defined as the belief that cultures constantly change through different racial and ethnic groups’ interactions, influences, and exchanges by not losing ethnic/group’s identity. This study aims to know the effect of conformity to Polyculturalism on college students from the outer region in Malang City. This research uses quantitative methods with purposive sampling. One hundred seventy-seven respondents gathered from regional organization members who live in regional dormitories. This research used five items of the Polyculturalism scale and eight items from the conformity scale. This study showed a positive correlation between conformity and Polyculturalism (R=0,372, P=0,000<0,005). The contribution of conformity to Polyculturalism is 13,8%.